2020
DOI: 10.1002/jgc4.1252
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the newborn screening education needs of families living in medically underserved areas

Abstract: Newborn screening (NBS) is a public health service available to all babies born in the United States (US). NBS is one of the first experiences families have in the US healthcare system with a new baby. A positive experience with NBS can give families a strong start to their child's health care and build trusting relationships with providers. A lack of easily accessible NBS education for families can exacerbate health inequalities through negative interactions with the healthcare system. Expecting Health, a mat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 13 publications
1
2
0
Order By: Relevance
“…We found providing baseline educational and explanatory text ensured that survey participants would have similar knowledge against which they could anchor and evaluate their own NBS experiences. The need to provide baseline knowledge to survey participants is consistent with a recent study by Evans et al which found that while 62% of parents indicated some familiarity with NBS, only about one-third of parents could accurately select a definition of NBS [ 9 ].…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…We found providing baseline educational and explanatory text ensured that survey participants would have similar knowledge against which they could anchor and evaluate their own NBS experiences. The need to provide baseline knowledge to survey participants is consistent with a recent study by Evans et al which found that while 62% of parents indicated some familiarity with NBS, only about one-third of parents could accurately select a definition of NBS [ 9 ].…”
Section: Discussionsupporting
confidence: 58%
“…Surveys are commonly used to gather a range of data on newborn screening (NBS) programs. In recent years, surveys have been employed to evaluate and improve NBS program processes including laboratory procedures [ 1 ], hospital blood spot collection [ 2 ], NBS results and follow-up communication [ 3 , 4 , 5 , 6 ], and parent education strategies [ 7 , 8 , 9 ]. An evolving area of research in newborn screening is the evaluation of public perceptions and parental knowledge and experiences with NBS [ 10 , 11 , 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…To identify potential needs and strategies for educating families about newborn screening, the Navigate NBS program conducted a nationwide needs assessment of 819 U.S.-based parents, expecting parents, individuals with NBS conditions, or family members of individuals with NBS conditions, with focus on those living inside of medically underserved areas (MUAs). As previously published, this assessment highlighted that individuals from MUAs reported less awareness of NBS and do not receive NBS education at the optimal time before birth, which could indicate that they experience inequities in NBS education [ 9 ]. In addition, the results from the needs assessment indicated that online, self-paced learning from trusted sources is the preferred communication and learning method for most families, particularly those that are harder to reach and from MUA.…”
Section: Methodsmentioning
confidence: 94%
“…Many families are not made aware of newborn screening prior to or at the time of their child’s birth, making it challenging for them to understand the importance of and possible outcomes of NBS, including follow-up testing. Complex health systems, siloed infrastructure, and limited resources exacerbate existing knowledge gaps around newborn screening and are often magnified among less educated and medically underserved populations, with research noting that infants of less educated parents are less likely to receive timely diagnosis and services [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Since awareness of NBS improves parental experiences, inadequate education about NBS could compound inequities faced by families of medically underserved areas (MUA). A survey conducted by Expecting Health and RTI International showed that families living within MUAs are less likely to receive NBS education prenatally and are less aware of NBS when compared to families living outside of MUAs [ 6 ].…”
Section: Introductionmentioning
confidence: 99%